Factors Determining Profitability Of Islamic Bank Empisire Study In Indonesia’s Sharia Banking - T. Muhammad Farizky (International Journal of Applied Finance and Business Studies, 2021)
This research was conducted to examine the effect of variable Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Operating Expenses Operating Income (BOPO), and Financing to Deposit Ratio (FDR) of Profitability (ROA). Profitability is used to measure the effectiveness of management based on results generated from the loan repayment and investment. The ratio is important for the bank's profitability is Return On Assets (ROA). Financial ratios that affect the ROA is the CAR, NPF, BOPO, and FDR. The sampling technique used was purposive sampling with the criteria of Islamic commercial bank serving the financial statements of the period December 2006-September 2010. The analysis technique used is the classical assumption of the analysis, multiple regression analysis and hypothesis test with a level of significance of 5%. The results of the research simultaneously (test F) states that the CAR, NPF, BOPO, and FDR jointly affect the profitability (ROA) of banks. While the results show that the correlation coefficient between profitability (ROA) of banks with 4 independent variables of 73.9%. And the result of research partially (t) states that the variable CAR and FDR did not have a significant positive effect on profitability (ROA) of banks. And variable BOPO NPF and significant negative effect on profitability (ROA) of banks.